The Effectiveness of Android-Based Simantb (TB Monitoring Information System) on Medication Compliance of Pulmonary TB Patients in Ende Regency, East Nusa Tenggara - Susanti, Maria; Arwani, Arwani; Widiyanto, Budi (Syntax Corporation Indonesia, 2025)
Tuberculosis (TB) is an infectious disease and one of the leading causes of death worldwide. One indicator of the TB control program's success is the treatment success rate. Various factors are believed to hinder the success of TB treatment, including therapy failure due to non-adherence, which is one of the main factors. Therefore, appropriate interventions are needed to monitor and evaluate TB patient medication adherence using suitable media that are easy to use and accessible anytime and anywhere through mobile health technology. This study aimed to analyze the effectiveness of the Android-based SIMANTB application on medication adherence in pulmonary TB patients. The research employed a Research and Development (R&D) design with a pre-experimental approach using a static group comparison, conducted over 28 days (1 month). The sampling technique used was simple random sampling, consisting of 30 respondents divided into intervention and control groups. Research data were analyzed using the Shapiro-Wilk and Mann-Whitney tests. The SIMANTB application was found to be highly suitable for tuberculosis patients, with material feasibility percentages of 93.06% and 93.75%. The use of the Android-based SIMANTB application significantly increased medication adherence in TB patients (p = 0.004). The development of the Android-based SIMANTB application is expected to provide a solution for health workers (doctors, nurses, TB officers) to support TB patients in monitoring and motivating their treatment, thereby increasing the success rate of treatment.